Leaf day respiration: low CO2 flux but high significance for metabolism and carbon balance. Issue 4 (2nd October 2017) - Tcherkez, Guillaume; Gauthier, Paul; Buckley, Thomas N.; Busch, Florian A.; Barbour, Margaret M.; Bruhn, Dan; Heskel, Mary A.; Gong, Xiao Ying; Crous, Kristine Y.; Griffin, Kevin; Way, Danielle; Turnbull, Matthew; et al.
Abstract : Contents 986 I. I. 987 II. II. 987 III. III. 988 IV. IV. 991 V. V. 992 VI. VI. 995 VII. VII. 997 VIII. VIII. 998 References 998 Summary: It has been 75 yr since leaf respiratory metabolism in the light (day respiration) was identified as a low‐flux metabolic pathway that accompanies photosynthesis. In principle, it provides carbon backbones for nitrogen assimilation and evolves CO2 and thus impacts on plant carbon and nitrogen balances. However, for a long time, uncertainties have remained as to whether techniques used to measure day respiratory efflux were valid and whether day respiration responded to environmental gaseous conditions. In the past few years, significant advances have been made using carbon isotopes, 'omics' analyses and surveys of respiration rates in mesocosms or ecosystems. There is substantial evidence that day respiration should be viewed as a highly dynamic metabolic pathway that interacts with photosynthesis and photorespiration and responds to atmospheric CO2 mole fraction. The view of leaf day respiration as a constant and/or negligible parameter of net carbon exchange is now outdated and it should now be regarded as a central actor of plant carbon‐use efficiency.